2014
DOI: 10.1038/onc.2013.562
|View full text |Cite
|
Sign up to set email alerts
|

Elafin drives poor outcome in high-grade serous ovarian cancers and basal-like breast tumors

Abstract: High grade serous ovarian carcinoma (HGSOC) and basal-like breast cancer (BLBC) share many features including TP53 mutations, genomic instability and poor prognosis. We recently reported that Elafin is overexpressed by HGSOC and is associated with poor overall survival. Here, we confirmed that Elafin overexpression is associated with shorter survival in 1000 HGSOC patients. Elafin confers a proliferative advantage to tumor cells through activation of the MAP kinase pathway. This mitogenic effect can be neutral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
45
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 66 publications
4
45
0
Order By: Relevance
“…5) Lastly, elafin may directly act on endothelial cells as a mitogenic molecule and promote angiogenesis. Informed by a recent publication, in which elafin was demonstrated to promote cancer cell proliferation in an ERK activation-dependent manner (35), we also found that elafin is capable of activating ERK in endothelial cells and promoting endothelial cell proliferation, migration and tube formation in a dose-dependent manner (Fig. 6).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…5) Lastly, elafin may directly act on endothelial cells as a mitogenic molecule and promote angiogenesis. Informed by a recent publication, in which elafin was demonstrated to promote cancer cell proliferation in an ERK activation-dependent manner (35), we also found that elafin is capable of activating ERK in endothelial cells and promoting endothelial cell proliferation, migration and tube formation in a dose-dependent manner (Fig. 6).…”
Section: Discussionsupporting
confidence: 81%
“…Although elafin is better known as an inhibitor of neutrophil elastase, a very recent study revealed that this endogenous inhibitor can also directly promote tumor cell proliferation by activating the ERK mitogenic signaling pathway (35). We performed Western blot analysis of HUVECs and showed that elafin dose-dependently enhanced ERK1/2 activation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As for its biological function in tumorigenesis, transcripts of PI3 are extremely abundant in glioblastoma patient samples and significantly correlated with dismal survival [ 29 ]. In ovarian and breast carcinoma, PI3 expression was also found to be transcriptionally up-regulated through activation of the NFκB and MEK/ERK signaling pathway, and correlate with unfavourable overall survival [ 30 ]. However, controversial report has already emerged that PI3 could suppress tumorigenesis through inhibition of elastase and thus could serve as a prognostic indicator in breast cancer [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, most of the information provided by whole genome sequencing (WGS) cannot be fully interpreted [55,56] . Despite the fact that there are over 800 new small molecules on developmental pipeline [57–59] , the number of drugable targets currently available in clinics is less than 30 [59,60] . The economic impact of a large scale application of WGS along with limited clinical applicability of information obtained from whole genome is suggestive for the utilization of alternative tools for diagnostic purposes.…”
Section: Diagnostic Platforms: Pcr Based Technologies and Massively Pmentioning
confidence: 99%